Bilateral asymmetry in joint torque during squat exercise performed by long jumpers - Kobayashi, Y.; Kubo, J.; Matsuo, A.; Matsubayashi, T.; Kobayashi, K.; Ishii, N. (The Journal of Strength and Conditioning Research, 2010)
This study aimed to examine the bilateral differences in movement and joint torques during the squat exercise by using kinematic and kinetic analyses. Eighteen long jumpers participated in this study. They performed 3 repetitions of the squat exercise with loads of 50, 70, and 90% of their 3 repetition maximum (3RM). During the exercise, their movement was recorded using a Vicon motion capture system. Ground reaction forces (GRFs) were simultaneously measured by 2 force platforms, one under each foot. On the basis of these position and force data, joint angles and torques for the hip, knee, and ankle were calculated using inverse dynamics. Results showed that the peak vertical and horizontal GRFs did not differ between the takeoff and non-takeoff legs in any loading condition. However, the maximal flexion angle and peak torque at hip showed significant differences between the limbs under all loading conditions (p < 0.05). In addition, the peak ankle torque in the takeoff leg was larger than that in the non-takeoff leg under a load of 90% of 3RM. These results indicate that joint torques may be bilaterally asymmetric when long jumpers perform the squat exercise, which should be considered when attempting to decrease the risk of injury.